The meaning and experience of bereavement support: A qualitative interview study of bereaved family caregivers - Kirby, E; Kenny, K; Broom, A; MacArtney, J; Good, P (Cambridge University Press, 2017)
Experiences of bereavement can be stressful and are frequently complicated by emotional, familial, and financial issues. Some—though not all—caregivers may benefit from bereavement support. While considered standard within palliative care services in Australia, bereavement support is not widely utilized by family caregivers. There is little research focused on the forms of bereavement support desired or required by family caregivers, how such care is viewed, and/or how bereavement support is experienced. This study examined the experiences of bereaved family caregivers and their impressions of and interactions with bereavement support. This paper reports on one aspect of a broader study designed to explore a range of experiences of patients and caregivers to and through palliative care. Focusing on experiences of bereavement, it draws on qualitative semistructured interviews with 15 family caregivers of palliative care patients within a specialist palliative care unit of an Australian metropolitan hospital. The interviews for this stage of the study were initiated 3–9 months after an initial interview with a family caregiver, during which time the palliative patient had died, and they covered family caregivers' experiences of bereavement and bereavement support. Interviews were digitally audiotaped and transcribed in full. A thematic analysis was conducted utilizing the framework approach wherein interview transcripts were reviewed, key themes identified, and explanations developed. The research identified four prevalent themes: (1) sociocultural constructions of bereavement support as for the incapable or socially isolated; (2) perceptions of bereavement support services as narrow in scope; (3) the “personal” character of bereavement and subsequent incompatibility with formalized support, and (4) issues around the timing and style of approaches to being offered support. Systematic pre-bereavement planning and careful communication about the services offered by palliative care bereavement support centers may improve receipt of support among bereaved family caregivers in need.